Immobilization of ionic liquids to covalent organic frameworks for catalyzing the formylation of amines with CO2 and phenylsilane. Issue 44 (6th May 2016) - Dong, Bin; Wang, Liangying; Zhao, Shang; Ge, Rile; Song, Xuedan; Wang, Yu; Gao, Yanan
Abstract : We presented the immobilization of ionic liquids on the channel walls of COFs using a post-synthetic strategy. Abstract : We presented the immobilization of ionic liquids on the channel walls of COFs using a post-synthetic strategy. The ionic [Et4 NBr]50% -Py-COF afforded a high CO2 adsorption capacity of 164.6 mg g −1 (1 bar, 273 K) and was developed as an effective heterogeneous catalyst for the transformation of CO2 into value-added formamides under ambient conditions.